2013
DOI: 10.1037/a0028066
|View full text |Cite
|
Sign up to set email alerts
|

Are you ready to jump? Predictive mechanisms in interpersonal coordination.

Abstract: When two or more individuals intend to achieve a joint outcome, they often need to time their own actions carefully with respect to those of their coactors. Online perceptual feedback supports coordination by allowing coactors to entrain with and predict each other's actions. However, joint actions are still possible when no or little online feedback is available. The current study investigated the interplay between higher-level planning processes and motor simulation in a joint action task where online feedba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 49 publications
9
87
0
Order By: Relevance
“…This suggests that mentally anticipating an interactive task may set the system in an enhanced readiness state that enables the participant to quickly gain dominance over his/her partner. This is in line with previous work showing that top-down predictive mechanisms play a crucial role in facilitating successful joint coordination (Knoblich and Jordan, 2003, Pecenka and Keller, 2011, Kourtis et al, 2012, Vesper et al, 2013.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that mentally anticipating an interactive task may set the system in an enhanced readiness state that enables the participant to quickly gain dominance over his/her partner. This is in line with previous work showing that top-down predictive mechanisms play a crucial role in facilitating successful joint coordination (Knoblich and Jordan, 2003, Pecenka and Keller, 2011, Kourtis et al, 2012, Vesper et al, 2013.…”
Section: Discussionsupporting
confidence: 93%
“…The second result of this analysis is that various signalling strategies perform similarly, but M5 is the best predictor of pairs' performance. Interestingly, our previous analyses (figure 8) have shown that most leaders use a signalling strategy that is well captured by M5, suggesting that they implicitly select an adaptive (if not optimal) way to convey information to their co-actors.…”
Section: Modelsmentioning
confidence: 99%
“…Ideomotor theories [2][3][4] propose the idea that ( predictive) simulative-like sensorimotor mechanisms such as internal forward models [5][6][7] support action perception. By extension, the motor coding of observed actions plays a major role in our ability to interact with others and to obtain efficient joint coordination [8]. The proposal is that we are able to predict, monitor and adapt to the behaviour of others by simulating their actions in our sensorimotor system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent rsif.royalsocietypublishing.org J R Soc Interface 10: 20130554 studies have investigated how humans mutually adjust and synchronize their behaviour during online joint actions, revealing the role of several mechanisms that range from automatic entrainment to action prediction [22,[57][58][59]]. An open research question is if and how sensorimotor interactions are influenced by the co-actors' goals and attitudes.…”
Section: Discussionmentioning
confidence: 99%